Implementation of Object Life-cycles in Relational Databases - Parakkat, Rohith; Řepa, Václav, 1958-; Kostrouchová, Veronika; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2024)
This thesis examines how to incorporate object life cycles with relational databases by applying the constraints that are defined through conceptual models. The aim of this study is to create a framework for managing dynamic object life cycles within relational databases guaranteeing integrity as well as consistency of data through enforced state transitions. UML Class diagrams and State charts alongside SQL based restrictions have been utilized in order to systematically translate dynamic object models into relational schemas during this research. The approach taken involves developing a strong conceptual model and implementing it practically in an Oracle Database along with PL/SQL functionalities were used during physical design stage as per necessity. Also, tools, technologies and modifications required for maintaining object identities during dynamic transitions through life cycle states are discussed. This was done so as to address key concerns like identity management issues, performance optimization among others besides illustrating its applicability within different business scenarios through demonstration. For instance, an online retail store case study has been conducted which validates the implementations efficiency in dealing with complex order management processes from creation up until delivery. Results showed successful handling of state transitions; effective resolution of identity; scalability under various scenarios. Through integration with real-world applications, this framework emphasizes its practical utility as well as its robustness and flexibility. This led to major achievements in the study whereby some challenges faced during implementation such as complex state transitions’ management and performance optimization were addressed successfully.
Therefore, this work contributes towards advancing Methodology for Modeling and Analysis Business Processes (MMABP) by providing a link between relational databases on one hand alongside conceptual models thus offering ideas for future improvements as well applications developments can be made based on them. The study has both theoretical and practical utility, making it significant for academic research as well as industry practices.
Vedoucí práce: Václav Řepa
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: information systems management [obor dipl. práce]; diplomové práce; master's theses